2015
DOI: 10.1039/c5ta01443c
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of sodium intercalation into disordered carbon

Abstract: Graphite, a predominantly chosen anode material for commercial lithium ion batteries (LIBs), has been reported to have negligible intercalation capacity as an anode for sodium ion batteries (NIBs). Disordered carbon exhibits high Na intercalation capacity and emerges as a leading candidate for NIB applications.However, the mechanism of Na + ion insertion into disordered carbon is still controversial. Here, wepropose an ab initio model for disordered carbon and investigate the intercalation mechanism of Na into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
216
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(246 citation statements)
references
References 44 publications
26
216
2
2
Order By: Relevance
“…This trend would be consistent with a recent ab initio study of sodium intercalation in disordered carbons [66], which predicts Na + ion intercalation beginning at ~0.7 V vs Na/Na + , attributing the higher values found in the literature (1.2-1.5 V vs Na/Na + ) to the strong bonding to oxygen functional groups on the materials surface. Another feature of these profiles is the absence of plateaus below 0.2 V, as no significant slope changes can be appreciated down to 0.003 V vs Na/Na + , as opposed to those typically observed for hard carbons [33,66]. This implies that only a small amount of Na + ions is inserted into nanopores/nanocavities in the EGs materials prepared.…”
Section: Mechanism Of Interaction With Na + Ions: Influence Of Oxygensupporting
confidence: 92%
“…This trend would be consistent with a recent ab initio study of sodium intercalation in disordered carbons [66], which predicts Na + ion intercalation beginning at ~0.7 V vs Na/Na + , attributing the higher values found in the literature (1.2-1.5 V vs Na/Na + ) to the strong bonding to oxygen functional groups on the materials surface. Another feature of these profiles is the absence of plateaus below 0.2 V, as no significant slope changes can be appreciated down to 0.003 V vs Na/Na + , as opposed to those typically observed for hard carbons [33,66]. This implies that only a small amount of Na + ions is inserted into nanopores/nanocavities in the EGs materials prepared.…”
Section: Mechanism Of Interaction With Na + Ions: Influence Of Oxygensupporting
confidence: 92%
“…They showed good electrochemical properties and cycling stability that compared favorably with previously reported disordered carbons [6,[19][20][21][22]. Additionally, we found that the role of the incorporated Febased nanoparticles in the electrochemical performance was due to Fe 3 C species which were passivated during the first few charge-discharge cycles.…”
Section: Introductionsupporting
confidence: 80%
“…Both, structural disorder and larger interlayer distance have been identified as factors that can improve Li ? and Na ? ion storage in carbonaceous electrodes [6,21,22].…”
Section: Processing and Morphologymentioning
confidence: 99%
“…[ 138,269, The storage of Na in carbon materials such as hard carbon, amorphous carbon, defected graphene, and functionalized graphite has been observed to be thermodynamically feasible. [ 325,326,274,276 ] In the early works by Doeff et al, they demonstrated that the extent of Na intercalation in carbon materials varies depending on the carbon structure; NaC 70 , NaC 30 , and NaC 15 were formed for graphite, petroleum coke, and Shawinigan black, respectively. [ 277 ] The inserted Na ions were also reversibly extracted from the carbon materials.…”
Section: Non-graphitic Carbonmentioning
confidence: 99%
“…Reproduced with permission. [ 276 ] Copyright 2015, Royal Society of Chemistry. g) Schematic of proposed Na storage mechanism.…”
Section: Non-graphitic Carbonmentioning
confidence: 99%